Consumer Perception of Private Label Products in Hungary - Robert Sandor Szucs; Kata Foldi (European Scientific Journal, ESJ, 2024)
Private labels have emerged as a significant force in the retail sector, particularly in the fast-moving consumer goods (FMCG) market. Their importance has grown as consumers increasingly prioritise value for money, often choosing these products over manufacturer-branded items. As a result, private labels have become a competitive tool for retailers, driving down costs and fostering customer loyalty through consistent quality at lower prices. This study investigates Hungarian consumers' perceptions of private label products, focusing on quality comparison between private labels and manufacturer brands. A comprehensive online survey was conducted between April and June 2024, with over 10,000 respondents providing insights into their shopping habits and quality assessments of private label products. The primary findings reveal that more than half of the respondents (52.3%) believe that the quality of private label products is comparable to that of manufacturer-branded products, while 14.7% even consider it superior. Interestingly, 33% of the respondents perceive private label products as inferior in quality, although the differences are often seen as slight. These perceptions are influenced by both objective and subjective factors, including brand loyalty, price, and packaging. Demographic analysis using Cramer's V coefficient indicates that factors such as age, gender, income, and education have minimal impact on these quality perceptions. However, slight variations were noted, with men more likely to view private label products as lower in quality compared to women. Additionally, those with higher education tend to rate the quality of private label products more favorably. The study also explores consumer behavior in hypothetical purchasing scenarios, finding that 85.9% of respondents would prefer a private label product if it were identical in content and produced by the same manufacturer as a more expensive branded option. This suggests a strong potential for growth in the private label sector, particularly if retailers continue to emphasize the quality and value of these products. In conclusion, the research highlights the growing trust in private-label products among Hungarian consumers, driven by the perception that these products offer comparable quality at lower prices. Retailers are advised to leverage this trust by expanding their private label offerings, particularly in categories where consumer preference is already strong, and by continuing to market these products effectively to different demographic groups.